Re-establishment of local populations of vectors of Chagas disease after insecticide spraying - Dohna, Heinrich Zu (2007)
1. Prevention of Chagas disease is mainly dependent on control of the insect vectors that transmit infection. Unfortunately, this control is not wholly successful and the vectors have been resurgent in some areas. Where re-infestation has occurred, it is important to understand the dynamics of the process. We investigated how a metapopulation framework can elucidate key aspects of re-infestation and thereby contribute to more efficient disease control. 2. Triatoma infestans, the main vector of Chagas disease, re-infested sites in three villages in north-west Argentina after community-wide insecticide spraying in October 1992. Ten surveys were carried out at 6-monthly intervals from November 1994 to May 1999. 3. Comparisons were made of different methods of estimating the sources of dispersal and the number of sites in which bug infestations became established. 4. The results indicated that (i) the number of dispersing Triatoma infestans from a given site was proportional to the number of bugs found at the site; (ii) there was a 6-month time lag between detection of a new infestation and dispersal events; (iii) the relationship between infestations and new establishments varied by season. 5. Three of 156 sites at which bugs were found were estimated to be the source of more than 50% of establishment events. These three sites were the only ones with large, persistent bug populations. 6. Synthesis and applications. To reduce the risk of human Chagas disease, identifying those few sites infested with large, persistent bug populations and targeting control measures at those sites should greatly improve the efficiency of vector control. The appropriate seasonal timing of vector control could also greatly increase its efficiency. Specific recommendations for the timing of insecticide spraying require further research to establish how the observed temporal pattern of bug establishment is associated with the seasonality of bug dispersal.